210. Improved Antimicrobial Utilization in the Emergency Department: Impact of a Point of Care Polymerase Chain Reaction Test for The Rapid Detection Influenza. (26th November 2018) - Williams, Jonathan; Mercuro, Nicholas; Vahia, Amit; Rizvi, Hira; Hameed, Mujtaba; Abreu-Lanfranco, Odaliz; Bhargava, Pallavi; Samuel, Linoj; Alangaden, George
Abstract: Background: Due to poor sensitivity, the FDA mandated that rapid influenza antigen (IAT) must be phased out by 2018. At our institution an on-site rapid influenza PCR (PCR) was implemented in emergency departments (ED) at the start of the 2016–2017 influenza season. The purpose of this study was to examine the impact of influenza PCR testing on antimicrobial utilization in the ED. Methods: This multicenter quasiexperimental study included adults over the age of 50 who were tested for influenza, and discharged from the ED. Subjects were matched 2:1 by age, sex, month of testing, and ED site. The pre-implementation group had IAT (January–April 2016) and the post-implementation had PCR testing (January–April 2017). The primary outcome was antiviral utilization. Other outcomes included diagnostic yield, test turnaround time (TAT), receipt of antibiotics, and 30-day revisit. Results: The PCR group of 116 patients (patients) were matched to 232 patients in IAT group (Table 1). Positive results for influenza were reported in 37.9% of PCR vs. 18.1% of IAT groups ( P < 0.001); TAT 0.95 (0.75–1.4) hours in PCR vs. 0.60 (0.40–0.85) hours in IAT group ( P < 0.001). Oseltamivir was initiated in the ED in 21% of PCR vs. 11% of IAT group ( P < 0.001). An additional 28% in PCR group received oseltamivir at ED discharge vs. 15% in IAT group ( P = 0.004). Antibiotics were administered in the ED to 8% in PCR group vs. 15% in the IAT group. A positive influenza test was associated with less antibiotic use OR 0.454 (95% CI 0.213–0.967), while abnormal chest radiograph (CXR) and WBC was associated with increased antibiotic use OR 3.667 (95% CI 1.743–7.715). The 30-day revisit was 3.8% and 10.8% in the PCR vs. IAT groups, respectively ( P = 0.034). Conclusion: Replacing IAT with PCR testing increased diagnostic yield for influenza and receipt of oseltamivir and decreased antibiotic utilization in the ED. Independent predictors for antibiotic use were abnormal CXR and WBC, while positive influenza testing was protective. Disclosures: All authors: No reported disclosures.